Historical Development of Non Governmental Organisations in Nepal - Singh, Sharada (Tribhuvan University Journal, 2013)
Non-Governmental Organizations are considered one of the major actors in the socio-economic development process. The northern countries and international agencies consider them as alternate institutional mechanisms for the transfer of resources to and also for understanding the reality of the developing countries. The southern countries are increasingly taking these entities as an effective vehicle for bringing social transformation, economic advancement, and furthering democratic governance. One of the major issues in developing countries like Nepal is how to uplift the economic status of rural people. For this, the government has accepted NGOs as development partners. It would be worthwhile to know about the historical development of Non Governmental Organisations in Nepal which is as below.